Modelling trust and contractual arrangements in a local economy. Issue 4 (19th May 2019) - Ayari, Dalel; Zaibet, Lokman
ABSTRACT: This article investigates trust among dairy value-chain actors to understand the innovative process in a local productive sector in Tunisia. It uses a sample of 45 smallholder farmers chosen randomly nearby existing collection centres in the region. A trust variable is constructed employing 11 ordinal variables based on principal component analysis, and institutional arrangements then modelled to examine the effect of trust on contracting decisions and cooperative membership. The results show that trust is defined by values such as "integrity", "competence", and "existence of credible information", which are preconditions to sustainable contracts. The article contributes to the growing literature which considers social capital, networking and trust as determinants of farmer's behaviour, as opposed to the classical model of rationality.